238 Molecular dissection of tumor-immune microenvironment factors associated with response to checkpoint inhibitor therapy in non-small cell lung cancer patients using nanostring digital spatial profiling. (10th December 2020) - Jabado, Omar; Couto, Suzana; Blum, Jordan; Franken, Patrick; Souza, Patricia Coutinho de; Jure-Kunkel, Maria; Pencheva, Nora; Higgs, Brandon; Sasser, Kate; Fereshteh, Mark
Abstract : Background: Understanding the dynamics of immune cells in the lung tumor microenvironment following immune checkpoint inhibitor (ICI) therapy is important for developing therapies tailored to patients with progressive disease. We sought to characterize protein and mRNA biomarkers in the tumor and stromal microenvironment in such patients with the Nanostring Digital Spatial Profiling (DSP) platform. DSP technology allows highly multiplexed profiling of proteins and RNA in a spatially resolved manner. Methods: FFPE non-small lung adenocarcinoma biopsies from 18 patients were sourced commercially (Capital Biosciences, MD). Patients had surgical resection of tumors then adjuvant chemotherapy. Upon progression, patients received monotherapy ICI (nivolumab or pembrolizumab). Once progressed on ICI, biopsies were performed and patients were then treated with platinum-doublet or single agent chemotherapy and followed until progression and/or death. Best overall response (BOR) and progression free survival (PFS) was available for ICI. FFPE tumors were sectioned and stained with anti-Pan-Cytokeratin, anti-PDL1 and anti-4-1BB (CD137) using standard immunofluorescence techniques. Twelve circular regions of 400 um in diameter containing tumor (PanCK+) and stromal (PanCK-) areas were selected per patient (figure 1 ). The technology uses a photocleavable DNA barcode strategy to multiplex antibodies and RNA in-situ hybridization probes. The GeoMX instrument was used to generate counts for 58 proteins and 84 RNAs on serial sections. Data normalization, linear modeling and survival analysis was conducted in R. Results: Lymphoid and myeloid markers were more abundant in stroma, indicating the microenvironment is diverse and confirming the DSP platform can segment adjacent cells. High levels of PDL1 protein in the tumor were correlated with T cell markers in the stroma (CD3, CD8, ICOS, IDO, OX40L) and inversely correlated with granulocytic (CD66b) and angiogenesis markers (CD34). We focused outcomes analysis on ICI response (9 PD/9 PR). OX40L protein was higher in patients with partial response and associated with delayed progression (figure 2 ). CD74 protein was associated with progressive disease during ICI therapy. CSF1R, CD4 and PECAM1 mRNA expression levels in stroma trended with progressive disease. Conclusions: In this study we recapitulated the role of OX40L as a marker for response to ICI 1 and CSF1R and PECAM1 in non-response to ICI. 2. 3 CD74 is a receptor for the pro-inflammatory cytokine (MIF) however CD74 ectodomain shedding may function as a decoy receptor. 4 These findings highlight how DSP can be used to probe the tumor microenvironment to identify pathways specific to NSCLC non-response for therapeutic target and biomarker development. Ethics Approval: Subjects provided informed consent to Capital Biosciences for genetic and protein analysis. Acknowledgements: Liang Zhang, Adrienne Whitman, Jennifer Hart, JingJing Gong of Nanostring Technologies. References: Massarelli E, Lam VK, Parra ER, et al. High OX-40 expression in the tumor immune infiltrate is a favorable prognostic factor of overall survival in non-small cell lung cancer. J Immunother Cancer 2019;7(1):351. Cannarile MA, Weisser M, Jacob W, Jegg AM, Ries CH, Rüttinger D. Colony-stimulating factor 1 receptor (CSF1R) inhibitors in cancer therapy. J Immunother Cancer 2017;5(1):53. Kuang BH, Wen XZ, Ding Y, et al. The prognostic value of platelet endothelial cell adhesion molecule-1 in non-small-cell lung cancer patients. Med Oncol 2013;30(2):536. Schröder B. The multifaceted roles of the invariant chain CD74-More than just a chaperone. Biochim Biophys Acta 2016;1863(6 Pt A):1269–1281.